Ni‐based Nanostructures as High‐performance Cathodes for Rechargeable Ni−Zn Battery. Issue 6 (6th April 2018) - Zhang, Haozhe; Wang, Rui; Lin, Dun; Zeng, Yinxiang; Lu, Xihong
Abstract: Aqueous rechargeable Ni−Zn battery with high capacity, low cost, and reliable safety has stimulated extensive interests for their promising applications in electric vehicles and portable electronics. The electrochemical properties of electrodes mostly determine the performances of the whole batteries. Currently, the capacities of the most developed cathodes are still far away from that of commercial Zn anode (820 mAh g −1 ), which is the major barrier for further boosting the energy density of Ni−Zn battery. In recent years, various Ni based materials like α‐Ni(OH)2, β‐Ni(OH)2, NiO and NiCo2 O4 have attracted considerable attention and been widely explored as cathode materials for Ni−Zn batteries. However, the poor conductivity and unsatisfactory cyclic stability of Ni‐based materials severely limit their implementation as robust cathodes for Ni−Zn batteries with high energy density and durability. To address these issues, substantial efforts have been made and great processes have been achieved. Herein, we highlight recent advances on rationally structural and componential design of Ni based electrodes for Ni−Zn batteries. The relationships between structures and performances as well as the mechanisms are also discussed. Finally, we present perspectives on the research of next‐generation electrodes with high electrochemical performances. Abstract : Recent advances on rationally structural and componential design of Ni based electrodes for Ni−Zn battery is highlighted. The relationships between structures and performances as well as the challenge on further high‐performance Ni−Zn battery are also discussed.